Unveiling Cancer Burden: An Epidemiological Study in a Tertiary Cancer Center, Thailand - Vichapat, Voralak; Hinon, Arunrat; Boonaob, Jittichai; Ukritanon, Pintumas; Meeniran, Banyong; Pansaksiri, Somsiri (Asian Pacific Journal of Environment and Cancer, 2023)
Objective: Cancer is a significant health burden. This research describes the current state of cancer epidemiology and trends in a tertiary cancer center in Thailand. Materials and Methods: Data from Saraburi Hospital electronic medical records (SBH), Thai cancer based (TCB), Pathological data, and Saraburi Provincial Public Health Office (PPHO) were merged using identification numbers and birthdates, establishing Saraburi hospital-based cancer registry. Cancers were categorized according to ICD10. Population at risk was obtained from the Thai national census department. Prevalence was calculated by dividing cancer cases by population in each district. Cause-specific incidence rates (CIRs) and mortality rates (CMRs) were estimated for cancer types and gender. Age-standardized incidence rates (ASIRs) and mortality rates (ASMRs) were calculated, weighting with 2020 Thai population data. Results: Between 2018 and 2022, 10,669 cases were identified in Saraburi province. Breast cancer was the most diagnosed cancer (17.6%), followed by colorectal (13.4%), lung cancer (7.8%), cervical cancer (5.9%), and liver cancer (5.5%). ASIR peaked at 509 (492-527) per 100,000 person-years in 2018 and decreased to 232 (220-244) per 100,000 person-years in 2022. Leading cancers for males were colorectal, lung, liver; females had breast, colorectal, cervical and lung cancer. 5-year prevalence was 1.7%. Males died mostly from lung and liver cancer (ASMR 30 and 29 per 100,000 person-years), while females died from breast cancer (ASMR 21 per 100,000 person-years). Life-time cumulative risk of death from cancer was 11%. Conclusion: This study reveals the cancer burden in Saraburi province, emphasizing the need for preventive strategies and resource allocations. The establishment of a cancer registry warrants future research.